Two-Year follow-up and remodeling kinetics of ChonDux hydrogel for full-thickness cartilage defect repair in the knee - Wolf, Matthew T.; Zhang, Hong; Sharma, Blanka; Marcus, Norman A.; Pietzner, Uwe; Fickert, Stefan; Lueth, Achim; Albers, G. H. Robert; Elisseeff, Jennifer H. (Cartilage, 2020)
Objective - To determine performance and repair kinetics of the ChonDux hydrogel scaffold for treating focal articular cartilage defects in the knee over 24 months. - Design - This assessor-blinded trial evaluates ChonDux hydrogel scaffold implantation in combination with microfracture in 18 patients across 6 sites. Male and female patients 18 to 65 years of age with full-thickness femoral condyle defects 2 to 4 cm2 in area were enrolled. Eligible patients received ChonDux treatment followed by rehabilitation. Defect volume fill was evaluated after 3, 6 (primary outcome), 12, 18, and 24 months by assessor blinded magnetic resonance imaging (MRI) analysis. Secondary outcomes were T2-weighted MRI relaxation time and patient surveys via visual analogue scale (VAS) pain and International Knee Documentation Committee (IKDC) knee function scoring. - Results - ChonDux maintained durable tissue restoration over 24 months with final defect percent fill of 94.2% ± 16.3% and no significant loss of fill volume at any time points. Tissues treated with ChonDux maintained T2 relaxation times similar to uninjured cartilage between 12 and 24 months. VAS pain scoring decreased between 1 and 6 weeks, and IKDC knee function scores improved by approximately 30.1 with ChonDux over 24 months. - Conclusion - ChonDux treatment is a safe adjunct to microfracture therapy and promotes stable restoration of full thickness articular cartilage defects for at least 24 months.